Transformasi Digital dalam Manajemen Hubungan Sekolah dan Masyarakat di Era Industri 4.0 - Ukat Suhaedi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze the implementation of digital transformation in managing school-community relationships in the era of Industry 4.0. Digital transformation is a response to technological advancements that influence communication patterns and community participation in education. Using a qualitative approach and a case study method, data were collected through in-depth interviews, participatory observations, and documentation at a vocational school that has integrated technology into its external relationship management. The findings indicate that digitalization of school communication and services enhances transparency, increases parental involvement, and fosters a collaborative culture between schools and communities. Despite challenges such as digital literacy gaps and limited infrastructure, digital transformation has proven effective in strengthening both social and institutional relations. This study recommends inclusive digital strategies, digital literacy training, and collaborative policies to optimize community engagement in educational processes.